Trichoscopic findings of Monilethrix. - Chieco, P. (European Journal of Pediatric Dermatology, 2015)
Monilethrix (M) is a hereditary disease linked to cyclical changes in the anagen phase: usually transmitted as an autosomal dominant trait M is linked to mutations of KRT81, KRT83 and KRT86 gene coding for the keratin of the hair. M can also be transmitted as an autosomal recessive trait due to mutations coding for the desmoglein 4 (1, 2). The trichoscopic examination allowed in our case to highlight the characteristic necklace appearance, which is usually observed on microscopic examination of the pulled hairs. The trichoscopic examination (3) makes it easier to confirm the diagnosis in children and also allows to identify more easily and quickly the family members with minimal forms of M. In our family so we could show that even two family members who had no obvious follicular keratosis were suffering from the same problem confirming the autosomal dominant inheritance.